1964
DOI: 10.1098/rspb.1964.0015
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic study of the assimilation of [ 15 N]-ammonia and the synthesis of amino acids in an exponentially growing culture of Candida utilis

Abstract: Ammonium phosphate labelled with 15 N has been used in a single quantitative experiment to trace the pathways of ammonia assimilation and amino acid synthesis in food yeast. Methods have been developed and are briefly described, whereby the free amino acids and amides, and the amino acid residues of the proteins, may be extracted from the yeast, separated by ion-exchange chromatography, quantitatively estimated, and the nitrogen of their α -amino groups specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
1

Year Published

1969
1969
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(35 citation statements)
references
References 5 publications
1
32
1
1
Order By: Relevance
“…3), glutamine-amide and glutamate seem to be the most important early products of ammonia assimilation in A. nidulans growing at low ammonia concentrations. However, the pattern of 5N labelling in the major amino acids in this study differed from the pattern of 5N labelling in major amino acids of ammonia assimilation by the GDH pathway in Candida utilis (Sims & Folkes, 1964), in which glutamate was initially more highly labelled than any other amino acid. Our results also differed from the pattern of labelling in the major amino acids of ammonia assimilation by the GSlGOGAT pathway in Lemna minor (Rhodes et al, 1980) and barley roots (Fentem et al, 1983), which showed that glutamine-amide was the first highly labelled compound.…”
Section: N Uptakecontrasting
confidence: 44%
See 3 more Smart Citations
“…3), glutamine-amide and glutamate seem to be the most important early products of ammonia assimilation in A. nidulans growing at low ammonia concentrations. However, the pattern of 5N labelling in the major amino acids in this study differed from the pattern of 5N labelling in major amino acids of ammonia assimilation by the GDH pathway in Candida utilis (Sims & Folkes, 1964), in which glutamate was initially more highly labelled than any other amino acid. Our results also differed from the pattern of labelling in the major amino acids of ammonia assimilation by the GSlGOGAT pathway in Lemna minor (Rhodes et al, 1980) and barley roots (Fentem et al, 1983), which showed that glutamine-amide was the first highly labelled compound.…”
Section: N Uptakecontrasting
confidence: 44%
“…Therefore, A. nidulans was grown on low ammonia and a quantitative analysis of the kinetics of l 5N incorporation into tissue amino acid pools was used. A similar approach has been successfully applied to the culture of Candida utilis, Lemna minor and Hordeum vulgare (Fentem et al, 1983; Rhodes et al, 1980; Sims & Folkes, 1964).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A more direct approach to establish the pathway of ammonia assimilation in higher plants is a quantitative analysis of the kinetics of '5N incorporation into tissue amino acid pools from an isotopically labeled nitrogen source. Such an approach has been successfully applied to cultures of Candida utilis growing under steady state conditions (3,21), demonstrating that in this organism the greater proportion of ammonia taken up from the medium is assimilated via GDH. Comparable studies with cultures of Lemna minor gave labeling data consistent with a two-compartment model in which ammonia is assimilated solely via the GS/glutamate synthase route (18 Sepaation of Nitrogen Compounds.…”
Section: Methodsmentioning
confidence: 99%